Angle Closure Glaucoma in Retinitis Pigmentosa - Chandni Pradhan; Simanta Khadka; Purushottam Joshi (Case Reports in Ophthalmological Medicine)
Background. Angle closure glaucoma (ACG) whether primary or secondary lens induced has rare occurrence in cases with retinitis pigmentosa (RP). Method. Five patients with history of diminished vision, ocular pain, and nyctalopia were clinically evaluated. Four patients had unilateral presentations of circumciliary congestion, corneal edema, and high intraocular pressure (IOP), while one had bilateral presentation, respectively. Anterior chambers were shallow; fundoscopy revealed the features of RP and gonioscopy affirmed closed angles in all the cases. The management strategies were individualized based on the specific ocular condition. Result. The raised IOP were not well controlled with conventional medical treatment. Neodymium yttrium aluminium garnet laser peripheral iridotomy (LPI) was performed in two patients and in the fellow eye in other two patients as a prophylactic measure. Phacoemulsification surgery with implantation of intraocular lens (IOL) was performed in three patients, whereas phacoemulsification only without IOL and trabeculectomy performed in one patient. Among them, two patients had subluxated lens, where one was managed with capsular tension ring and the other was left aphakic, respectively. However, the vision was not improved significantly in these patients. Conclusion. RP may be associated with ACG in rare instances. In these patients, angle closure-related high IOP can have a detrimental effect on the pre-existing visual impairment. However, this can be prevented by thorough clinical examination and timely intervention in those susceptible eyes.